Role of Sustainability in Marketing Strategies: In the Context of Digital and Direct Marketing - Valliappan Raju, Assoc. Prof. Dr.; Md Rom Bin Tamjis, Prof Dr. (International Journal of Engineering and Technology, 2019)
Time has seen the diverse periods of promoting procedure. Out of which, supportability is the key issue which has risen in advertising procedure over the time. In prior period of 1970s, biological issues have developed as another worldview in promoting technique. At that point in one decade from now, social issues grabbed the lime light and rose alongside biology. Reassessment of the issues brought about development of green or ecological issues in advertising procedure and now the manageability in showcasing technique has turned into the focal point of consideration of the scientists. Thusly, the destinations of this paper are, first, to survey and comprehend ideas of advertising system and manageability, also, to talk about development of maintainability in showcasing methodology and ultimately, to examine the eventual fate of supportability promoting technique.Â